2017
DOI: 10.1038/s41598-017-04484-0
|View full text |Cite
|
Sign up to set email alerts
|

Transplanted adipose-derived stem cells can be short-lived yet accelerate healing of acid-burn skin wounds: a multimodal imaging study

Abstract: The incidence of accidental and intentional acid skin burns is rising. Current treatment strategies are mostly inadequate, leaving victims disfigured and without treatment options. Here, we have shown that transplantation of adipose-derived stem cells (ASCs) accelerates the process of acid burn wound-healing. Pre-conditioning of ASCs using ascorbic acid (AA) or hypoxic conditions provided additional benefit. While the wounds were ultimately healed in all mice, histological analysis revealed that, in non-transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 58 publications
(56 reference statements)
1
28
0
Order By: Relevance
“…7 Although it was initially thought that the therapeutic effects of MSCs depend on their capabilities for cell replacement, many studies have demonstrated that paracrine activity is the predominant mechanism by which MSCs participate in tissue repair. [8][9][10] It was shown that by the secretion of different bioactive molecules, MSCs may support endogenous stem cell proliferation, Dovepress Dovepress 1654 Dabrowska et al reduce apoptosis, promote angiogenesis, and modulate immune reactions. [11][12][13][14][15] Previous studies have focused on characterizing MSC-produced soluble factors, ie, cytokines, chemokines, and growth factors, but it has been recently documented that MSCs release also large numbers of extracellular vesicles (EVs).…”
Section: Introductionmentioning
confidence: 99%
“…7 Although it was initially thought that the therapeutic effects of MSCs depend on their capabilities for cell replacement, many studies have demonstrated that paracrine activity is the predominant mechanism by which MSCs participate in tissue repair. [8][9][10] It was shown that by the secretion of different bioactive molecules, MSCs may support endogenous stem cell proliferation, Dovepress Dovepress 1654 Dabrowska et al reduce apoptosis, promote angiogenesis, and modulate immune reactions. [11][12][13][14][15] Previous studies have focused on characterizing MSC-produced soluble factors, ie, cytokines, chemokines, and growth factors, but it has been recently documented that MSCs release also large numbers of extracellular vesicles (EVs).…”
Section: Introductionmentioning
confidence: 99%
“…Preparation of allograft ADS. The ADS were obtained from adipose tissue within the abdominal region of healthy adult rats as described previously 57,58 . About 3 cm 3 of adipose tissue was manually minced and subjected to digestion with 0.1% collagenase type I solution for 25 min at 37 °C, and then centrifuged.…”
Section: Resultsmentioning
confidence: 99%
“…The cell pellets were suspended in Dulbecco's Modified Eagle's Medium (DMEM) plus 20% fetal bovine serum and then seeded into T-75 flasks that contained DMEM, 20% fetal bovine serum, 100 U/ml penicillin, and 100 µg/ml streptomycin. The ADS were characterized for mesenchymal stem cell markers by flow cytometry, as reported previously 57,58 .…”
Section: Resultsmentioning
confidence: 99%
“…It has known that MSCs are often stressed and begin to die after being transplanted, releasing various cytokines and growth factors beneficial for wound healing 15 . In this study, we did not find any significant difference between the SVF-and MSC-treated groups.…”
Section: Discussionmentioning
confidence: 99%